2004
DOI: 10.4319/lo.2004.49.3.0716
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative coupling during gut passage in marine deposit‐feeding invertebrates

Abstract: We tested for oxidative coupling of phenolic materials, including organic contaminants and tyrosine, in gut fluid from marine deposit-feeding invertebrates. A phenolic metabolite (pyrenol) of a polycyclic aromatic hydrocarbon (PAH), which can arise during accumulation by deposit-feeding invertebrates, was found to participate in oxidative coupling reactions to organic matter in gut fluid. Gut fluid from four species of marine deposit-feeding invertebrates (three polychaetes and one holothuroid) catalyzed oxida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 54 publications
1
2
0
Order By: Relevance
“…Pyrene was not detectable by HPLC/F in tissue samples after enzymatic hydrolysis, probably due to precipitation with organic matter during the enzymatic hydrolysis procedure, as is the case of SFS measurements. This is in agreement with the study of Giessing and Mayer (2004) who observed coprecipitation of pyrene with the matrix components after the centrifugation.…”
Section: Using 1-hydroxypyrene Concentrations To Characterize Pah Expsupporting
confidence: 93%
“…Pyrene was not detectable by HPLC/F in tissue samples after enzymatic hydrolysis, probably due to precipitation with organic matter during the enzymatic hydrolysis procedure, as is the case of SFS measurements. This is in agreement with the study of Giessing and Mayer (2004) who observed coprecipitation of pyrene with the matrix components after the centrifugation.…”
Section: Using 1-hydroxypyrene Concentrations To Characterize Pah Expsupporting
confidence: 93%
“…Another risk factor is the ability of benthic organisms to metabolize these compounds. Some aquatic invertebrates, for example, certain polychaetes, are able to degrade PAHs [ 27 , 28 ], but many others are not able to do this well, for example, bivalve mollusks [ 29 ]. PAHs are metabolized by phase 1 enzymes of cytochrome P450 mixed function oxygenase system, and excreted as hydroxylated metabolites [ 30 ].…”
Section: Resultsmentioning
confidence: 99%
“…Since both polychaetes defecate at the sediment surface, it is possible that gut passage of PAH-contaminated sediment may have reduced PAH bioavailability in the defecated sediment. Giessing & Mayer (2004) showed that gut fluid from marine deposit-feeding polychaetes catalyzed oxidative coupling of pyrene metabolites to organic matter and subsequently decreased the bioavailability. The authors suggested that this reaction, which leads to covalent binding of PAHs, represents a sink for PAHs.…”
Section: Discussionmentioning
confidence: 99%